OPTIMIZING FUNCTION AND PHYSICAL ACTIVITY IN ASSISTED LIVING THROUGH EVALUATION OF THE ENVIRONMENT AND POLICIES. (11th November 2018) - Holmes, S
Abstract: To evaluate the impact of the environment and policies on physical activity of AL residents' two measures were developed: The Environment Assessment to Optimize Function and Physical Activity and the Policy Assessment to Optimize Function and Physical Activity. This study included 106 settings from three states. Based on Rasch analysis, there was evidence of item reliability of both measures, test retest reliability (r= .71; and .86, p<.05) and evidence of construct validity based on Rasch analysis and fit of the items to the concept. Policy Assessment to Optimize Function and Physical Activity was associated with hospitalizations (r=-.22, p=.04) and emergency room visits (r=-.25, p=.03). There was evidence for the reliability and validity of these measures and use of these measures can guide the senior industry in making changes so as to assure that residents' function and physical activity are optimized and maintained and they are able to age in place.